Long-term effects of land reform on human capital accumulation: Evidence from West Bengal - Klaus Deininger; Songqing Jin; Vandana Yadav (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
We use data on inter-generational gains in educational attainment by some 500,000 individuals in 200 West Bengal villages to explore gender-differentiated impacts of land reform on human capital accumulation at the individual level. While there are significant gains (of about 0.3 years for males) in the immediate post-reform generation, their magnitude pales in comparison to second-generation effects of between 0.85 and 1.2 years that appear irrespectively of the land reform modality. Moreover, there are possibly significant spillover benefits on villagers who did not directly benefit from reform. Placebo tests and alternative specifications support robustness of the results. By contrast, levels of beneficiary productivity and welfare remain far below average, something that could likely be avoided if land reform beneficiaries would receive full ownership rights - rather than being recognized as permanent share tenants and if restrictions on transferability of land were abandoned.
Keywords: O12; O15; Q15; 330; India; land reform; long-term effects; human capital; Bodenreform; Humankapital; Bildungsabschluss; Generationenbeziehungen; West Bengal